CRISPR: A Promising Tool for Cancer Therapy - Mohammad-Rafiei, Fatemeh; Safdarian, Esmat; Adel, Bashir; Vandchali, Noushin R.; Navashenaq, Jamshid Gholizadeh; Gheibihayat, Seyed Mohammad (Current Molecular Medicine, 2023)
The clustered regularly interspaced short palindromic repeats system, called CRISPR, as one of the major technological advances, allows geneticists and researchers to perform genome editing. This remarkable technology is quickly eclipsing zinc-finger nucleases (ZFNs) and other editing tools, and its ease of use and accuracy have thus far revolutionized genome editing, from fundamental science projects to medical research and treatment options. This system consists of two key components: a CRISPR-associated (Cas) nuclease, which binds and cuts deoxyribonucleic acid (DNA) and a guide ribonucleic acid (gRNA) sequence, directing the Cas nuclease to its target site. In the research arena, CRISPR has been up to now exploited in various ways alongside gene editing, such as epigenome modifications, genome-wide screening, targeted cancer therapies, and so on. This article reviews the current perceptions of the CRISPR/Cas systems with special attention to studies reflecting on the relationship between the CRISPR/Cas systems and their role in cancer therapy.
Keywords: cancer